Mantle hydration and the role of water in the generation of large igneous provinces. Issue 1 (December 2017) - Liu, Jia; Xia, Qun-Ke; Kuritani, Takeshi; Hanski, Eero; Yu, Hao-Ran
Abstract The genesis of large igneous provinces (LIP) is controlled by multiple factors including anomalous mantle temperatures, the presence of fusible fertile components and volatiles in the mantle source, and the extent of decompression. The lack of a comprehensive examination of all these factors in one specific LIP makes the mantle plume model debatable. Here, we report estimates of the water content in picrites from the Emeishan LIP in southwestern China. Although these picrites display an island arc-like H2 O content (up to 3.4 by weight percent), the trace element characteristics do not support a subduction zone setting but point to a hydrous reservoir in the deep mantle. Combining with previous studies, we propose that hydrous and hot plumes occasionally appeared in the Phanerozoic era to produce continental LIPs (e.g., Tarim, Siberian Trap, Karoo). The wide sampling of hydrous reservoirs in the deep mantle by mantle plumes thus indicates that the Earth's interior is largely hydrated. The genesis of large igneous provinces (LIPs) remains controversial. Here, the authors examine the water contents of picrites from the Emeishan LIP and find that despite high water contents, the elevated temperature and trace elements suggest a mantle plume from a hydrous deep reservoir rather than subduction zone related.